PROCESS OF PURIFICATION OF WASTE COOKING OIL USING MONITORING (MORINDA CITRIFOLIA) AND KAOLIN AS ADSORBENT - Alfian Putra; S Sariadi; Reza Fauzan; Yaumil Akmalia H; T Taufik (Jurnal Sains dan Teknologi Reaksi, 2023)
The use of cooking oil repeatedly at high temperatures will cause the quality and nutritional value of fried foods to decrease, which can have a negative impact on consumer health. Repeated use will increase the levels of free fatty acids (ALB) in cooking oil so that it will have a negative impact on the health of people who consume it or use it as a heating medium (frying). The adsorption process is carried out by contacting used cooking oil and adsorbent in the composition Because of this, the idea arose to use noni as an adsorbent for refining used cooking oil by means of adsorption using a mixture of noni (M) and kaolin (K) by varying the composition and contact time. The function of this adsorbent is generally to absorb impurities, odors and chemical substances that are toxic in used cooking oil. Ascorbic acid contained in noni fruit also functions as an anti-oxidant, namely a substance that is able to neutralize the peroxide groups contained in used cooking oil. The function of this adsorbent is generally to absorb impurities, odors and chemical substances that are toxic in used cooking oil. Ascorbic acid contained in noni fruit also functions as an anti-oxidant, namely a substance that is able to neutralize the peroxide groups contained in used cooking oil. The adsorption process is carried out by contacting used cooking oil and adsorbent in the composition Ascorbic acid contained in noni fruit also functions as an anti-oxidant, namely a substance that is able to neutralize the peroxide groups contained in used cooking oil. The adsorption process is carried out by contacting used cooking oil and adsorbent in the composition (100:0 ; 75:25 ; 50:50 ; 25:75 ; 0:100) for 30, 60, 90 and 120 minutes respectively with activated and unactivated kaolin as the control variable. The oil after adsorption was then observed for changes in acid number, peroxide value, moisture content, impurities content and color intensity. In several studies, the quality of oil recovered from used cooking oil showed a slightly blackish color, making the oil look less attractive. The use of kaolin as a bleaching earth in refining used cooking oil is due to the high SiO2 content in kaolin, which is expected to improve the color of used cooking oil, especially to improve the color of the recovered oil, so that it approaches the quality of standard cooking oil used in the market.Keywords: adsorbent; free fatty acids; noni; used cooking oil; kaolin